Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.2147/ccid.s114450
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerance of an injectable medical device containing stable hybrid cooperative complexes of high- and low-molecular-weight hyaluronic acid: a monocentric 16 weeks open-label evaluation

Abstract: BackgroundAn injectable medical device containing stable hybrid cooperative complexes of high- and low-molecular-weight hyaluronic acid (HA) has been developed with characteristics suited for a global improvement of facial esthetics.ObjectiveTo evaluate the HA product performance in improving some key facial esthetic features. The study employed clinical scales, subjective evaluations, and facial skin objective measurements.MethodsA single Italian site treated 64 female subjects aged 38–60 years, with injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 15 publications
1
33
0
Order By: Relevance
“…They were used in comparative in vitro studies and using different cellular models [24,35]. They have recently been commercially available for aesthetic medicine use, and with reports have shown that HCCs were particularly suitable for the treatment of skin laxity of malar and submalar areas, and for counteracting facial aging [36,37]. Such clinical outcomes were also beneficial for the improvement of skin elasticity in areas such as temples, forehead, hands, inner arms and neck.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…They were used in comparative in vitro studies and using different cellular models [24,35]. They have recently been commercially available for aesthetic medicine use, and with reports have shown that HCCs were particularly suitable for the treatment of skin laxity of malar and submalar areas, and for counteracting facial aging [36,37]. Such clinical outcomes were also beneficial for the improvement of skin elasticity in areas such as temples, forehead, hands, inner arms and neck.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Several patients in this study were noted to have retained effect of filler more than 5 years postinjection, with one case even noted at the 10‐year follow‐up, while others had lost effect at the 6‐month visit. Many different combinations of HAG filler exist, and the effect profile may be related to the degree of cross‐linkage as well as the molecular weight of the HAG filler used . More recent formulations include mixtures of low‐ and high‐molecular weight HAG, as well as cross‐linked and autocross linked combinations which promise a longer duration of effect .…”
Section: Discussionmentioning
confidence: 99%
“…Many different combinations of HAG filler exist, and the effect profile may be related to the degree of cross‐linkage as well as the molecular weight of the HAG filler used . More recent formulations include mixtures of low‐ and high‐molecular weight HAG, as well as cross‐linked and autocross linked combinations which promise a longer duration of effect . Long‐term data on the duration and side effect profile of these combination fillers are yet to be determined …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations